Cisplatin-Induced DNA Damage Activates Replication Checkpoint Signaling Components that Differentially Affect Tumor Cell Survival - Wagner, Jill M. (American Society for Pharmacology and Experimental Therapeutics, 2009)
Cisplatin and other platinating agents are some of the most widely used chemotherapy agents. These drugs exert their antiproliferative effects by creating intrastrand and interstrand DNA cross-links, which block DNA replication. The cross-links mobilize signaling and repair pathways, including the Rad9-Hus1-Rad1-ATR-Chk1 pathway, a pathway that helps tumor cells survive the DNA damage inflicted by many chemotherapy agents. Here we show that Rad9 and ATR play critical roles in helping tumor cells survive cisplatin treatment. However, depleting Chk1 with small interfering RNA or inhibiting Chk1 with 3-(carbamoylamino)-5-(3-fluorophenyl)-N-(3-piperidyl)thiophene-2-carboxamide (AZD7762) did not sensitize these cells to cisplatin, oxaliplatin, or carboplatin. Moreover, when Rad18, Rad51, BRCA1, BRCA2, or FancD2 was disabled, Chk1 depletion did not further sensitize the cells to cisplatin. In fact, Chk1 depletion reversed the sensitivity seen when Rad18 was disabled. Collectively, these studies suggest that the pharmacological manipulation of Chk1 may not be an effective strategy to sensitize tumors to platinating agents.